Pengaruh Model Inkuiri Terbimbing Berbasis Lingkungan Terhadap Keterampilan Proses Sains Siswa Kelas V dalam Pembelajaran IPA di SDN 12 Singkawang - Neti Mariyanti; Emi Sulistri; Rien Anitra (Lembaga Pengembangan Kinerja Dosen, 2023)
. This research aims to determine the effect of an environmentally based guided inquiry model on students' science process skills. Quasi Experimental research was conducted with a Pretest-Posttest Control Group Design- nonequivalent control group. Saturated sampling technique was used to determine the treatment class, namely class VA as the control class and class VB as the experimental class. Data collection was carried out using a written test in the form of short answer questions. For the data results obtained by the experimental class, the average pre-test score was 56 and the post-test score was 70. Meanwhile, the data results obtained by the control class had an average pre-test score of 52 and post-test score 58. Based on statistical tests using the SPSS test. effect size (ES), probability value (significance) is 0.89, so the Ho hypothesis is rejected, meaning the guided inquiry model has a significant effect on students' Science Process Skills.